Influence of Infection Delay on the Covid-19 Pandemic with Vaccination Control: Modeling and Simulation - Rami Raad Saadi; Hassan F. Al-Husseiny (Ibn Al-Haitham Journal for Pure and Applied Sciences)
In this work, we formulate a mathematical model of the killer COVID-19 pandemic with time delay and some governmental measures that include vaccine subsidies to understand the dynamic behavior of COVID-19. For the dynamic study, a new model, SV1V2IR was used purposed in which infectious individuals were divided into five sub compartments. Our aim is to construct a more reliable and realistic model for a complete mathematical and computational analysis and design of different control strategies for the proposed deterministic model. We first obtain the basic reproduction number for the model is computed using a next-generation technique to predict the future dynamics of the pandemic. The local stability of the model was also investigated at each equilibrium point. The findings show that the time delay can produce a Hopf bifurcation for a SV1V2IR  model. The obtained numerical results are discussed and predict through graphs.